NERACA KARBON, EMISI DAN SERAPAN HISTORIS CO2 KARENA PERUBAHAN PENGGUNAAN LAHAN DI KABUPATEN BANYUASIN, SUMATERA SELATAN - Firyadi Firyadi; Widiatmaka Widiatmaka; Asdar Iswati; Ardiansyah Muhamad; Budi Mulyanto (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2018)
Land use change is the cause of carbon loss from land. The loss of this carbon becomes a source of carbon dioxide (CO2) in the atmosphere that can cause global warming. Intensive land use and land cover occurred in Kabupaten Banyuasin from 2004-2014. The purpose of this study. to create carbon balance, emissions and sequestration of CO2 during the period of 2004 - 2014 in Banyuasin Regency caused by land use change and land cover change. The method used to create carbon balance using land use change matrix, carbon calculation of each carbon pool by allometric method, destructive sample and organic C by Walkley and Black method. Stock diference method for analysis of changes in carbon storage, CO2 emissions and CO2 sequestration. The results of this study indicate that the 2004-2014 carbon balance in Banyuasin Regency is negative, with a carbon loss of 22,033,277 tons with an average annual carbon loss of 2,203,327 tons. CO2 sequestration of 29,298,966 tons and CO2 emissions 118,044,141 tons, while net emissions 88,745,175 tons. Average net CO2 emissions from above ground carbon pools, carbon necromassa pools, litter carbon pools and underground carbon pools are 7 tonnes ha-1 year-1, whereas CO2 emissions from organic soil C 0.61 tonnes ha- 1 year-1. The largest contributor of CO2 emissions in Banyuasin Regency are sequentially caused by changes in peat swamp forests, secondary mangrove forests, primary mangrove forests and secondary swamp forests. While the source of sequestration is the change of monoculture rubber peat, oil palm, rubber monoculture and shrubs.